Stress Management: Your Lifelines - Joe Pergola; Suzanna Smith (EDIS, 2003)
People who deal with stress have “lifelines” to others who can help. Support is very important. People with support have fewer stress-related health problems. These “lifelines” are systems of social support. Social support is help given by friends, family, and neighbors in times of crisis or emergency, or on a daily or occasional basis. Community services and religious congregations are also sources of social support. This document is FCS2081A, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida. First Publication: June 1989 as FCS2081. Reviewed: August 1999. Revised: January 2002.